Menggali makna keluarga Allah dalam dunia Alkitab dan surat Efesus: analisis historis-biblis - Parihala, Yohanes (KURIOS (Jurnal Teologi dan Pendidikan Agama Kristen), 2021)
This study aims to find the historical and theological vision of the Church’s concept as the household of God. Historically, the idea of family or household was a heritage of ancient society. Theologically, the idea was related to God in Jesus Christ as a cornerstone and foundation for the Christian community living in the world. This concept is very relevant as the way for Christians to face various crises in life. This research uses qualitative research methods through a literature study approach. The data analysis uses the historical-theological criticism, which starts from the idea of family and household in the New Testament world, covering the context of Israel in the Bible, Greco-Roman society, and New Testament writings, then interpretation the meaning of the community of the believer as the household of God in Ephesians 2:19. Argumentatively, I argue that the idea of God’s household has a strong influence on the relevance of being Church today in addressing various social problems, both problems of life crises and social inequalities, as well as various conflicts. Abstrak Kajian ini bertujuan untuk menemukan visi teologi-historis konsep persekutuan beriman sebagai keluarga Allah. Secara historis, gagasan keluarga atau rumah tangga telah mengakar di dalam konteks masyarakat di masa lampau. Secara teologis, konsep ini dihubungkan dengan Allah di dalam Yesus Kristus, yang dimaknai sebagai batu penjuru dan dasar dari kehidupan komu-nitas Kristen hingga di masa kini. Gagasan ini masih tetap relevan sebagai jalan bagai umat Kristen merespons berbagai persoalan dan krisis dalam kehidupan. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan. Analisis data menggunakan metode kritik historis-teologis yang dimulai dengan analisis konsep keluarga atau rumah tangga di dalam dunia Perjanjian Baru, meliputu konteks Israel dalam Alkitab, masyarakat Yunani-Romawi, tulisan-tulisan PB, dan penafsiran makna komunitas beriman sebagai keluarga Allah di dalam Efesus 2:19. Secara argumentatif, penulis menegaskan bahwa konsep keluarga Allah sangat relevan dan mempunyai dampak bagi keberadaan gereja hingga di masa kini, terutama dalam menghadapi berbagai persoalan sosila, krisis kehidupan, dan berbagai konflik.